Dopamine@Nanodiamond as novel reinforcing nanofillers for polyimide with enhanced thermal, mechanical and wear resistance performance. Issue 7 (18th January 2018) - Qin, Songlv; Cui, Mingjun; Qiu, Shihui; Zhao, Haichao; Wang, Liping; Zhang, Afang
Abstract : In this study, to achieve a homogeneous dispersion of nanodiamond (ND) in a polyimide (PI) matrix and a strong interfacial adhesion between ND and the PI matrix, a biomimetic nondestructive dopamine chemistry was employed for surface modification of ND. Abstract : In this study, to achieve a homogeneous dispersion of nanodiamond (ND) in a polyimide (PI) matrix and a strong interfacial adhesion between ND and the PI matrix, a biomimetic nondestructive dopamine chemistry was employed for surface modification of ND. FTIR and Raman spectroscopy studies revealed that self-polymerization of dopamine could produce thinner polydopamine (PDA) layers on the ND surface via spontaneous oxidation and the intermolecular cross-linking reaction of PDA molecules. The structure and morphology of PDA–ND were studied by FTIR, SEM, and Raman spectroscopy, which verified the π–π interactions between PDA and ND. The facile dispersion of PDA–ND in a polyamic acid prepolymer made it possible to obtain PI/ND composites with no obvious ND aggregation. The effect of PDA–ND nanoparticles on the thermal, mechanical and tribological properties of the resulting PI/PDA–ND composites were evaluated, and the results showed that the incorporation of PDA–ND could increase the hardness, tensile strength, storage modulus, as well as the wear resistance properties. PI/PDA–ND composites prepared in this study showed that PDA–ND is a promising nanoreinforcing filler for PI composites.